Divorce, Remarriage and Child Cognitive Outcomes: Evidence from Canadian Longitudinal Data of Children. Issue 8 (16th November 2020) - Ferrer, Ana; Pan, Yazhuo (Annie)
ABSTRACT: This study investigates the role of divorce and remarriage on cognitive outcomes of children. Using the rich panel data information from the National Longitudinal Survey of Children and Youth (NLSCY), collected biennially since 1994, we investigate the association between children's math and reading performance and divorce and remarriage relative to intact families. We find that children who stay-in or move-to non-intact families have lower reading scores than those who stay in intact families. Although initial findings indicate that family structure has an overall small effect on children's math performance, we find a differential impact of family structure on Math performance across gender and cultural heritage.